Comparison of learning outcomes of first year medical students in physiology post-laboratory discussion using two types of facilitation - Chan, Remedios Dee
Objective: The University of Sto. Tomas Faculty of Medicine and Surgery Department of Physiology post-laboratory presentations are principally teacher-let. Physiology student surveys revealed that being a laboratory conference presenter was highly beneficial to learning while being an audience was perceived as least beneficial. The study sought to ask which teaching strategy was more effective in maximizing learning by comparing the learning outcome of first year medical students in laboratory conferences in Physiology under two types of facilitation in term, of knowledge gained, skills in class participation, problem-solving and attitudes like attentiveness and motivation. It also determined other correlates like demographic characteristics, type of topics order of presentation of type facilitation, previous exposure to student-led activities, upcoming examination in other subjects, that affected the performance of students in both types of discussions. Methodology: The study used a quasi-experimental cross-over research design involving 511 first year medical students taking up Physiology in the school year 2007-2008. Quantitative descriptive design using written pre- and post-test, a questionnaire, and a rating scale were used to see the effect of the interventions during a Physiology laboratory conference. Result: Significant score improvement was seen during the teacher-led discussion. The type of pre-medical school and upcoming examinations were also significant predictors of score improvement. Students? self-assessment gave better responses on problem-solving skills and motivation during the student-led discussion while there was no difference in their responses in class participation and attentiveness in both teacher- and student-led discussions. Conclusion and Recommendation: This study concluded that there was greater knowledge gained in a teacher-led discussion. It supported the findings that novice students tended to lean from their teachers during their early years of study. The students also perceived significant gain in problem-solving skills and motivation during student-led discussion making it a promising teacher strategy.